PENGARUH KEPRIBADIAN, KOMPENSASI DAN GAYAKEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN (Studi padaPerum LPPNPI (AirNav Indonesia) Cabang Pratama Semarang) - Lady Nurdianti, 14.05.51.0246; Rijanti, Tristiana (Students' Journal of Economic and Management, 2018)
This study aims to analyze the influence of personality, compensation and transformational leadership style on the performance of employees of LPPNPI Public Corporation (AirNav Indonesia) Pratama Semarang branch. Respondents in this study consisted of 85 people of LPPNPI Public Corporation (AirNav Indonesia) Pratama Semarang branch. Data analysis used is validity test, reliability test and multiple linear regression analysis. Data processing was carried out using SPSS 19. The results showed that simultaneously independent variables had an effect on the dependent variable. Partially, personality variables have a significant positive effect on employee performance, compensation variables have no effect on employee performance, transformational leadership style variables have a significant positive effect on employee performance. Keyword :Personality, Compensation, Transformational Leadership Style and Employee Performance.